Long-Term Follow-Up of Multilayer Amniotic Membrane Transplantation (MLAMT) for Non-Traumatic Corneal Perforations or Deep Ulcers with Descemetocele - Berguiga, M.; Mameletzi, E.; Nicolas, M.; Rivier, D.; Majo, F. (Klinische Monatsblätter für Augenheilkunde, 2013)
Background: To evaluate the long-term efficacy of multilayer amniotic membrane transplantation for reconstruction of epithelium and stroma in non-traumatic corneal perforations (less than 2 mm) or deep ulcers with descemetocele.Design: Retrospective, non-comparative, interventional case series.Patients and Methods: Eleven consecutive patients with non-traumatic corneal perforations or deep corneal ulcers with descemetocele refractory to conventional treatments: herpetic or zoster keratitis (n = 4), Sjögrenʼs syndrome (n = 2), rosacea (n = 1), hydrops (n = 1), mucous membrane pemphigoid (n = 1), bacterial keratitis (n = 1) and perforation after protontherapy for melanoma (n = 1). Intervention was: multilayer amniotic membrane transplantation with cryopreserved amniotic membrane. Complication rate and clinical outcome were evaluated in this long-term follow-up.Results: Mean follow-up was 32 months (12 to 60). Integration of the multilayer amniotic membrane was obtained in 10 cases after one year. Corneal epithelium healed above the membrane in 10 cases within 3 weeks and remained stable after 32 months in 9 cases. Thickness of the stroma was increased and remained stable during the follow-up in 9 cases. In one case herpetic keratitis recurred with a corneal perforation. The clearing of the amniotic membrane was gradually obtained over a period of 11 months. Complications occurred in 15 % of the eyes during the long-term follow-up.Conclusion: Multilayer amniotic membrane transplantation is a safe and efficient technique for a long restoration of the corneal integrity after non-traumatic corneal perforations or deep corneal ulcers with descemetocele. Long-term prognosis of these eyes depends of the gravity of the initial disease.
Keywords: multilayer amniotic membrane transplantation; non-traumatic corneal perforation; deep ulcer; descemetocele